The Anxiety of Being Asian American: Hate Crimes and Negative Biases During the COVID-19 Pandemic - Tessler, Hannah (American journal of criminal justice, 2020)
In this essay, we review how the COVID-19 (coronavirus) pandemic that began in the United States in early 2020 has elevated the risks of Asian Americans to hate crimes and Asian American businesses to vandalism. During the COVID-19 pandemic, the incidents of negative bias and microaggressions against Asian Americans have also increased. COVID-19 is directly linked to China, not just in terms of the origins of the disease, but also in the coverage of it. Because Asian Americans have historically been viewed as perpetually foreign no matter how long they have lived in the United States, we posit that it has been relatively easy for people to treat Chinese or Asian Americans as the physical embodiment of foreignness and disease. We examine the historical antecedents that link Asian Americans to infectious diseases. Finally, we contemplate the possibility that these experiences will lead to a reinvigoration of a panethnic Asian American identity and social movement.